أثر العوامل الاجتماعية والاقتصادية والصحية في الهجرة الخارجية لرأس المال البشري في سورية - حيدر, عز الدين; ابراهيم, عمار (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدف الباحث إلى التعرف على مفهوم هجرة رأس المال البشري, ومعرفة الأسباب الداخلية الرئيسية وراء انتشار ظاهرة هجرة رأس المال البشري في سورية, من خلال دراسة أثر مجموعة من العوامل الاقتصادية والاجتماعية والصحية (معدل البطالة, معدل الوفيات, العمر المتوقع عند الولادة, نسبة التشغيل على عدد السكان (15 عاماً وأكثر), ومعدل التضخم, معدل تخرج طلاب المرحلة الجامعية الأولى, ومعدل تخرج طلاب الدراسات في الجامعات السورية) في معدل هجرة رأس المال البشري, بالاعتماد على البيانات الاحصائية خلال الفترة الواقعة بين عامي 1990-2010, وتوصل الباحث إلى أهم النتائج التالية: أن ارتفاع معدل التضخم يؤدي إلى ارتفاع معدل هجرة رأس المالي البشري, في حين أن انخفاض معدل البطالة يؤدي إلى ارتفاع معدل الهجرة, إلا أن ارتفاع نسبة التشغيل يؤدي إلى ارتفاع طفيف بمعدل الهجرة ويعزى ذلك إلى أن أغلب الفئات الشابة تتابع دراساتها خارج البلد بعد التخرج من المرحلة الجامعية الأولى, في حين أن ارتفاع العمر المتوقع عند الولادة يؤدي إلى انخفاض شديد في معدل هجرة رأس المال البشري, وأن ارتفاع نسبة الخريجين من المرحلة الجامعية الأولى يؤدي إلى ارتفاع معدل هجرة رأس المال البشري, ويعزى ذلك إلى أن النسبة الأكبر من الخرجين تفضل الهجرة باحثة عن العمل أو لمتابعة تعليمهم في الدول الأخرى, في حين أن ارتفاع نسبة خريجي طلاب الدراسات يؤدي إلى انخفاض معدل هجرة رأس المال البشري, ويعزى ذلك إلى أنهم فضلوا متابعة تحصيلهم العلمي داخل البلد, مما يقلل من فرص هجرتهم بسبب متابعة تعليمهم, أو بسبب ازدياد وعيهم لأهمية تواجدهم داخل البلد This study aimed at identifying the concept of human capital migration and identifying the main internal causes behind the phenomenon of human capital migration in Syria by studying the impact of a range of economic, social and health factors (unemployment rate, death rate, life expectancy, (15 years and more), the rate of inflation, the graduation rate of undergraduate students and the graduation rate of students of studies in Syrian universities) on the rate of human capital migration, based on the data between 1990 and 2010. The researcher reached the following main results: High inflation leads to l The high rate of migration of the human capital, while the low unemployment rate leads to the high rate of migration, but the high rate of employment leads to a slight increase in the rate of migration and this is because most of the young groups pursue studies outside the country after graduation, The increase in life expectancy at birth leads to a sharp drop in the rate of human capital migration. The high percentage of university graduates leads to a high rate of human capital migration. This is due to the fact that the largest proportion of graduates prefer immigration to work or to follow them in countries Other, while a The increase in the proportion of graduates of study students leads to a decline in the rate of human capital migration. This is due to the fact that they prefer to continue their education within the country, thus reducing their chances of emigration due to the continuation of their education or because of their increasing awareness of the importance of their presence within the country.